Electricity Intensity and Unemployment in South Africa: A Quantile Regression Analysis - Ruzive, Tafadzwa; Mkhombo, Thando; Mhaka, Simbarashe; Mavikela, Nomahlubi; Phiri, Andrew (International Journal of Energy Economics and Policy, 2018)
Our study investigates the relationship between electricity intensity and unemployment in South Africa. Our mode of empirical investigation is the quantile regressions approach which has been applied to quarterly interpolated time series data collected between 2000:01 and 2014:04. As a further development to our study, we split our empirical data into two sub-samples, the first corresponding to the pre-financial crisis period and the other corresponding to the post-financial crisis period. Our empirical results point to electricity intensity being significantly and positively correlated with unemployment in periods before the crisis at all estimated quantiles, whereas this relationship turns significantly negative in periods subsequent to the crisis at all quantile levels. In other words, since the financial crisis, increased electricity intensity (i.e. lower electricity efficiency) appears to reduce domestic unemployment rates, a result which indicates that policymakers should be discouraged from implementing electricity conversation strategies and encouraged to rely on environmental friendly methods of supplying electricity. Keywords: Electricity intensity; Unemployment; South Africa; SSA; Quantile regressions. JEL Classifications: C31; C51; E24; Q43. DOI: https://doi.org/10.32479/ijeep.6158